Metacognitive Instruction Enhances the Effectiveness of Corrective Feedback: Variable Effects of Feedback Types and Linguistic Targets. Issue 2 (20th February 2018) - Sato, Masatoshi; Loewen, Shawn
Abstract: This study explored the impact of metacognitive instruction provided in conjunction with corrective feedback, investigating the moderating effects of two types of implicit corrective feedback (input‐providing conversational recasts vs. output‐prompting clarification requests) that targeted English third‐person singular – s and possessive determiners his / her . Adult English as a foreign language learners from intact classes ( N = 83) were assigned to four conditions: metacognitive instruction plus input‐providing recasts, input‐providing recasts only, metacognitive instruction plus output‐prompting clarification requests, and output‐prompting clarification requests only. Metacognitive instruction enhanced the effect of conversational recasts that otherwise had minimal impact but had no added benefit for clarification requests that supported language development without metacognitive instruction. Although the effect of metacognitive instruction was not moderated by linguistic structure, effectiveness of corrective feedback depended on linguistic target. Although corrective feedback in general impacted third‐person singular – s more, the comparison of feedback types showed that the advantageous effect of clarification requests was found only for possessive determiners, the more salient and communicatively valuable structure. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible via the IRIS Repository athttps://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .